MAQASID SYARIAH DAN PEMBANGUNAN HAK ASASI MANUSIA - Kurniawan, Robby (UIN Sunan Kalijaga Yogyakarta, 2018)
Human rights, must be recognized, is a term that still debated in Islamic studies until now. This stems from the repetition statements: Human Rights (UDHR) are not born from the womb of Islam. This article attempts to find a way out of the complexity of the debate, with questions; How to build a conceptual relationship between sharia, as the concept of Islamic law, with Human Rights? The question about